Comparative and cross-cultural education in the context of cultural diversity - Jerzy Nikitorowicz (Studia z Teorii Wychowania)
The aim of the article is to draw attention to the new challenges and tasks of the two sub-disciplines of education (comparative and cross-cultural education) in the face of widespread cultural diversity, growing nationalisms and the ongoing war in Ukraine. The author assumes that cultural diversity is the civilisational wealth of mankind, therefore these sub-disciplines are confronted with the challenge of conducting, in a conscious and responsible manner, the educational activities that provide knowledge about their own culture and other cultures and their representatives. The author presents numerous problems that these subdisciplines have to address, ranging from the awareness of the value of inherited culture to the need and necessity to transcend one's own ethnocent3rism and sociocentrism. He poses numerous questions, refers to historical facts, points to the need for the emancipation of national memories, etc. What is seen as the fundamental challenge for comparative and cross-cultural education is the one of liberating oneself from hyper-subordination and the ability to engage in a dialogue free from propaganda that intends to dominate the thinking and attitudes oriented towards cognition, understanding, cooperation, collaboration.